Use of Internet among Rural Teenagers: Pattern of Usages, Awareness and Associated Health Hazards - Jobayer, Mohammad; Sultana, Rabeya; Anwar, Sk Serjina; Afroz, Zeenat; Akter, Nadira; Chowdhury, Mahbuba; Rashed, Asif; Farhana, Nasreen; Islam, Lohani Md Tazul; Hussain, Dewan Azmal (Bangladesh Medical Journal, 2019)
Internet has become an essential tool for communication, information, and entertainment and use of internet is increasing among the teenage group. This cross sectional study was conducted among 385 teenagers from rural area of Narayanganj district in Bangladesh to evaluate the practice of internet use, their awareness about the beneficial and harmful effects and associated physical and psychological health hazards. The study reached its various findings from the view point of rural area of our country. The study population was chosen purposively; data were collected using a semi structured questionnaire regarding their knowledge and various practice of internet use relating to the objectives. Most of the respondents were students and came from lower middle class family. Majority of the study people recently started to use internet and they were mostly light or moderate user in terms of time spending. Mobile phone was used as device by 84.7% people for their internet browsing. Teenagers used internet mainly for entertainment (42.1%) and social networking (35.6%) purpose and not much for learning or education. They were aware about the beneficial and the harmful effects of internet use especially abuses. Commonly experienced physical health hazards by them were headache (11.7%), straining of eyes or blurring of vision (10.7%) and skipping meals or change in eating behavior (9.1%), and among the psychological hazards, restlessness or agitation (8%) and depression (5.2%) were stated. It may be concluded that use of internet among teenagers of rural area of our country is at modest level associated with a few health hazards but the merits of internet based networking is yet to be revealed by them. Bangladesh Med J. 2017 Sep; 46 (3): 69-73